Telomere dynamics in chronic myeloid leukaemia - Gil, Marcel Eduardo (My University, 2014)
Telomeres are regions of tandem repeats at the ends of chromosomes ensuring chromosome stability or inducing replicative senescence when critically short. Telomerase extends telomeres and its catalytic subunit, telomerase reverse transcriptase is tightly regulated at multiple levels. Cancerous cells prevent telomere-mediated senescence to attain unlimited proliferation, in most cases by enhancing telomerase activity. Chronic myeloid leukaemia is characterised by the translocation, t(9;22), in haematopoietic stem cells. The resulting fusion protein exhibits constitutive tyrosine kinase activity in the cytoplasm, promoting cellular proliferation, inhibiting apoptosis and impeding cell adhesion. Changes in telomere biology have been observed in chronic myeloid leukaemic cells. The current study aimed to investigate telomere biology in 18 chronic myeloid leukaemia patients at various time intervals from date of diagnosis. Although telomeres were significantly shorter in patients compared to controls, results point to complex telomere dynamics in the malignancy. Increased telomerase activity did not necessarily accompany telomere lengthening and increased transcription of the telomerase catalytic subunit was not necessarily indicative of telomerase activity. Ultimately the current study could not detect any trends between telomere length, telomerase activity and telomerase catalytic subunit expression in chronic myeloid leukaemia patients. Together with inherent patient-to-patient variation and the high cost per assay, measurement of telomere biology does not appear to hold prognostic value in chronic myeloid leukaemia and does not warrant inclusion into a routine test repertoire.
Keywords: Chronic myeloid leukemia.; Telomere.; Blood $x Diseases.